Secure Telemedicine: Biometrics for Remote and Continuous Patient Verification - Agrafioti, Foteini; Bui, Francis M.; Hatzinakos, Dimitrios (Journal of Computer Networks and Communications, 2012)
The technological advancements in the field of remote sensing have resulted in substantialgrowth of the telemedicine industry. While health care practitioners may now monitor theirpatients’ well-being from a distance and deliver their services remotely, the lack of physicalpresence introduces security risks, primarily with regard to the identity of the involved parties. The sensing apparatus, that a patient may employ at home, collects and transmits vital signalsto medical centres which respond with treatment decisions despite the lack of solid authenticationof the transmitter’s identity. In essence, remote monitoring increases the risks of identity fraud inhealth care. This paper proposes a biometric identification solution suitable for continuous monitoringenvironments. The system uses the electrocardiogram (ECG) signal in order to extract uniquecharacteristics which allow to discriminate users. In security, ECG falls under the category ofmedical biometrics, a relatively young but promising field of biometric security solutions. In thiswork, the authors investigate the idiosyncratic properties of home telemonitoring that may affectthe ECG signal and compromise security. The effects of psychological changes on the ECGwaveform are taken into consideration for the design of a robust biometric system that can identifyusers based on cardiac signals despite physical or emotional variations.